2024
DOI: 10.5114/jhk/182888
|View full text |Cite
|
Sign up to set email alerts
|

Resistance Training Practices of Brazilian Olympic Sprint and Jump Coaches: Toward a Deeper Understanding of Their Choices and Insights (Part III)

IRINEU LOTURCO,
Santiago Zabaloy,
Lucas A. Pereira
et al.

Abstract: In the final part of this three-article collection on the training strategies of Brazilian Olympic sprint and jump coaches, we provide a detailed description of the resistance training methods and exercises most commonly employed by these speed experts. Always with the objective of maximizing the sprint and jump capabilities of their athletes, these experienced coaches primarily utilize variable, eccentric, concentric, machine-based, isometric, complex, and isoinertial resistance training methods in their dail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 176 publications
0
2
0
Order By: Relevance
“…However, the influence of RT is not uniform; it varies according to the athlete's competitive level, sex, and the specific demands of their sport. Notably, the impact of RT is more pronounced in national elite athletes than their international counterparts, suggesting that the latter may require more advanced and individualized training interventions ( Loturco et al, 2024 ). Further meta-analysis revealed that RT had a more significant impact on local sports tasks compared to global activities, indicating its differential influence on sport-specific performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the influence of RT is not uniform; it varies according to the athlete's competitive level, sex, and the specific demands of their sport. Notably, the impact of RT is more pronounced in national elite athletes than their international counterparts, suggesting that the latter may require more advanced and individualized training interventions ( Loturco et al, 2024 ). Further meta-analysis revealed that RT had a more significant impact on local sports tasks compared to global activities, indicating its differential influence on sport-specific performance.…”
Section: Discussionmentioning
confidence: 99%
“…Resistance training (RT) is widely acknowledged as a vital component in enhancing athletic performance, significantly influencing an athlete's sport-specific abilities and skills ( Abdi et al, 2019 ; Loturco et al, 2024 ; Spieszny et al, 2022 ; Thiele et al, 2020 b). Its diverse nature allows for a broad spectrum of benefits, adaptable to various athletic needs and goals ( Harries et al, 2012 ; Loturco et al, 2023a ; Saeterbakken et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%